Konstruksi Identitas ISIS Melalui Digital Media “Youtube” di Indonesia - Rachmawati, Tety; Karisma, Gita (POLITEA, 2018)
The Post-Cold War turning to globalizations era, evokes a variety of issues, particularly, identity and religion. Some scholars had stated strongly the relations between religion and identity. Some, not all, religious actors demonstrate terrorism trait and performed symbol which was identically close with Islam. One of the phenomenon of Islamist terrorism was Islamic State in Iraq and Syria (ISIS). ISIS was known as terrorist bringing Islamic doctrine that has mission to jihad (holy struggle). Islam was not different with other religions, it promote peace and harmony in the world. On the contrary, ISIS spread fear and intimidation. ISIS not only did terror in Iraq, Syria, or the Middle East countries but also in other countries such as countries in Europe, Asia, and America.  This article attempted to answer how ISIS construct their transnational identity through digital media, Youtube. The method was using qualitative approach and data collection technique was literature study. The result of this paper described a process of building up ISIS identity cross national border and explained how could ISIS convince and recruit member beyond the state in case their movement in digital media, Youtube. Key words: Identitas, ISIS, Youtube